TINJAUAN KECERDASAN YUSUF BERDASARKAN KECERDASAN SPIRITUAL (SPIRITUAL INTELLIGENCE), KECERDASAN EMOSIONAL (EMOTIONAL INTELLIGENCE), KECERDASAN INTELEKTUAL (INTELLECTUAL INTELLEGENCE) DAN KETANGGUHAN (ADVERSITY QUOTIENT) - Purwanto, Agus (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
One of the people chosen by God to prepare a country and its people in fulfilling His plan, that person was Joseph. Joseph as the maker of history and the link that connects the Book of Genesis to the Book of Exodus, was chosen by God to fulfill His plan, not by going through a smooth road, but there are many steep and abyss as a life experience to go through. The inclusion and guidance of God, made Joseph have something "special", namely intelligence. Intelligence is not only in terms of intellectual intelligence, but various intelligence is given by God to enable Joseph to live his life. This paper reviews Joseph's Intelligence based on Spiritual Intelligence, Emotional Intelligence, Intellectual Intelligence and Adversity Quotient. Joseph's life experience, privileges and obedience ultimately brought success in fulfilling God's plan to preserve the life of a nation.